Bibliometric Mapping: Development of Pedagogical Competency Research in Community Education - Nurul Hayati; Babang Robandi; Ihat Hatimah (STAI Hubbulwathan Duri, 2024)
The need to grasp the newest trends and improvements in education necessitates examining the development of pedagogical competency studies in community education. The aim of this research is to describe the development of studies on pedagogical competence in community education. This study employs bibliometric analysis with Vosviewer for network visualisation, overlay, and density analysis. This study technique is suitable for extensively examining the evolution of studies on pedagogical competency from 2014 to 2023. The bibliometric mapping results using Vosviewer showed varying advances in research publications on pedagogical competency in community education from 2014 to 2023. Only 253 of the total publications indexed by Google Scholar, or 508 documents, fulfilled the criterion. The year with the largest publishing growth development was 2018, with 38 publications (15.0%), and the year with the lowest publication growth development was 2022, with 14 publications (5.5%). The study of pedagogical competencies in community education is essential to keep up with the latest trends and improvements in education. In addition, a more in-depth analysis highlighted the themes that appeared most frequently in the publications during the research period. This research provides insight into trends and patterns in the study of pedagogical competence in community education, which can help guide efforts to develop pedagogical competence in this area.